Análise da alteração da qualidade das águas superficiais impactadas por usinas hidrelétricas recém implantadas na Amazônia - Matheus Ribeiro Coura (2020)
The construction of dams and artificial reservoirs aims to serve several human purposes, such as water supply, irrigation, flood control, recreation, fishing and electricity generation. Although the construction of reservoirs has the objective of promoting social well-being, many environmental impacts are associated with the implementation of dams, the alteration of the quality of surface water being one of the most notable impacts. This work used statistical techniques to assess surface water quality in reservoirs and downstream stretches of four major hydroelectric power plants (HPP) located in the Amazon (Belo Monte, Jirau, Santo Antonio de Jari and Teles Pires). The multivariate statistical technique used (Cluster Analysis) was efficient to identify distinctions between the dendrograms obtained for the pre and post-filling phases of the four projects, indicating changes in water quality. The MannWhitney U non-parametric statistical hypothesis test (5% significance level) allowed the identification of parameters that presented significant alteration after reservoir filling. Considering the four hydroelectric projects, after systematizing and organizing the database, a total of 45 monitoring points and 54 distinct water quality parameters were analyzed. Thirtysix parameters presented more frequently significant alteration (in 40% or more of monitoring points of an HPP). Of the 36 parameters, 14 significantly changed more frequently in more than one HPP: water temperature, pH, dissolved oxygen, electrical conductivity, redox potential, transparency, total dissolved solids, chlorophyll a, thermotolerant coliforms, alkalinity, total phosphorus and calcium, sulfate and sulfide ions. These parameters were considered the most important to explain the change in water quality after reservoir filling. All points located in the reservoirs (41 points) and river stretches immediately downstream of the dams (4 points) showed significant changes in water quality. Thus, impacts on surface waters along the whole length of the reservoirs and also on river stretches downstream of the dams were observed. Monitoring points located in smaller water bodies in the pre-filling phase, close to the confluence with the main rivers, and which were flooded by the reservoirs in the post-filling phase (forming the beginning of arms or dendritic regions in the reservoirs), stood out in terms of the number of water quality parameters that changed significantly.